Fulfilment of Family Needs With Disabilities - Noviati, Elis; Sukmawati, Ima; N, Rudi Kurniawa; Ningrum, Dena Mustika; Firdaus, Fidya Anisa (Alta Dharma Publisher, 2022)
Background: The level of independence of children with disabilities has a greater dependence on the family. Family is an important component to meet the needs of children with disabilities. Objective: This study aims to describe the needs of families with children with disabilities. Method: The method uses quantitative with descriptive research design. The research sample used a non-probability sampling technique with a purposive sampling approach at SLBN Ciamis as many as 156 with a sampling of (N=60) being parents with children with disabilities. This research was conducted in February 2022. The research instrument used the .Assessment .Of Family .Needs-FNS .questionnaire. Result: The results showed that the needs of families with children with disabilities, in order from the highest to the lowest scores, were the need for information (83.3%) and the need for professional support (81.7%), the need to explain to others (68.3%), financial need (65.0%), child care (41.7%), support and social (33.3%). Conclusion: Conclusion: If the need for information and professional support is met, parents will know better how to care for and develop their children's potential optimally. Keywords: Children .with .Disabilities, .Family .Needs, .Parent